Critical thinking building the basics - Smith, Donald E. P.; Knudsvig, Glenn M.; Walter, Timothy L. (Wadsworth Publishing Company, 1998)
This text is a guide to critical thinking and composition courses. It covers just the basics of critical thinking using an acronym called TCDR (Topic, Class, Description, Relevance). The text grounds the student in the basics of the technique and uses exercises to drive lessons home. It also shows students how to use critical thinking across the curriculum.